PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI PECEL NDESO YU DJASMO SOLO - Nikolaus Toding, Bambang Mursito & Istiqomah (Universitas Slamet Riyadi, 2018)
This research aims to determine the effect of product quality, price and promotion of purchasing decisions in Pecel Ndeso Yu Djasmo either partially or simultaneously. This type of research is associative research. The population in this study is Pecel Ndeso Yu Djasmo consumers in Solo Quare Solo, the number of samples in this study 97 people. Sampling technique in this research using nonprobability sampling method. Data were obtained by spreading the questionnaire. Data analysis technique using multiple linear regression analysis, t test, F test, and coefficient of determination. The result of data analysis found that product quality, price, and promotion have significant effect to purchasing decision simultaneously or partially. The result of coefficient of determination (R2) equal to 84,0%, while the rest equal to 16,0% influenced by other factor not included in this research.Keywords: price, product, promotion, purchase decision